THE EFFECT OF COMPETENCE, TRAINING AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE AT PT. CITIBANK - Khaerani, Reny; Mohamad Trio Febriyantoro; Zulkifli; Dede Suleman; Fendi Saputra; Yohanes Totok Suyoto (Asosiasi Dosen Muda Indonesia, 2022)
This study aims to determine and analyze the effect of Competence, Training and Career Development on the performance of employees of PT. Citibank Jakarta branch. The type of research used is quantitative. The analytical method used is multiple linear regression analysis. In this study, the population and sample were all employees working at the Jakarta branch of PT. Citibank, totaling 40 people. The method of determining the sample is saturated sampling. Data was obtained by distributing questionnaires online using the Google form. The test method uses multiple linear regression and is processed using SPSS version 23. The results show that from the results of the F test that the variables Competency, Training and Career Development have a positive and significant effect on employee performance. The results of the research based on the t test show that only the Competency and Career Development variables have a positive and significant effect on employee performance. While the training variable has a negative and insignificant effect on employee performance. So it can be concluded that competence and career development can improve performance or quality for a company in achieving its goals.